Parametric investigation of thermal vacuum evaporation of aluminum and silver thin films on silicon substrate - Balidoy, Quennie Lynn G.
Aluminum and silver films were deposited using the JEE 4x thermal vacuum evaporator of the Department of Mining, Metallurgical and Materials Engineering, University of the Philippines. The deposited films were characterized in terms of sheet resistance, morphology, thickness, crystal orientation, and adhesion. A full 2^4 factorial design with replicated centerpoint runs was employed to determine the effects of the deposition parameters namely weight of the evaporant, radial distance of the source to specimen, applied current and chamber pressure, on the thickness and adhesion of the silver films. Based on the ANOVA, all factors have significant effects on the film thickness at 95% confidence level. The film thickness was found to increase with increase in the weight of the evaporant, decrease in the radial distance, increase in applied current and decrease in the chamber pressure. Interaction between radial distance and pressure is significant at 99% confidence level. At 95% confidence level, two-factor interactions between weight and current, weight and pressure and radial distance and current became significant. An interactive first order model was fitted to the experimental data: Y = 379.89 + 94.34X1 - 93.64X2 + 36.81X3 - 75.84X4 + 41.52X1X3 - 41.61X1X4 + 35.85X2X3 + 72.33X2X4 where Y = film thickness in angstroms; X1 = weight of the evaporant, coded variable = (weight in mg - 35)/15; X2 = radial distance from the source to specimen, coded variable = (radial distance in cm - 7.75)/1.45; X3 = applied current, coded variable = (applied current in A - 35)/5; X4 = chamber pressure, coded variable = chamber pressure in microtorr - 5)/3. Sheet resistance values were used to estimate the film thickness. For aluminum films, a constant sheet resistivity value of 4.187 μohm-cm was used based on sheet resistance and AFM thickness measurements. However, for silver films, thickness was estimated using a power relationship between sheet resistance and thickness as sheet resistivity was found to vary with film thickness. Estimated thickness values of the deposited aluminum films ranged from 70-1600 angstroms while for silver films, thickness ranged from 80-1000 angstroms. They were plotted against weight of the evaporant and inverse of the square of the radial distance of the source to specimen. The plots revealed linear dependence of thickness with the weight of the evaporant and the inverse of the square of the radial distance of the source to the specimen. Morphological characterization of the films through FESEM and AFM revealed that deposited aluminum films contain semi-angular grains while silver films have ellipsoidal shaped grains. It was also shown that some of the films are still in the island grown and coalescence stage within the thickness range produced. XRD and TEM characterization of the films confirmed the polycrystallinity of the films. Adhesion test through scotch tape test showed that aluminum films show higher adherence to the silicon substrate than silver films. It was also generally observed that silver films with thickness between 500-800 angstroms have lesser adhesion on the substrate than films with less than 500 angstrom thickness.